Advances in coral aggregate concrete and its combination with FRP: A state-of-the-art review. Issue 6 (April 2021) - Zhou, Wen; Feng, Peng; Yang, Jia-Qi
As an economical and eco-friendly construction material, coral aggregate concrete (CAC) plays an increasingly important role in emerging marine engineering applications. CAC fully utilizes local raw materials on remote islands. Due to the porous structure and low-strength characteristics of coral aggregates, CAC exhibits unique characteristics compared to ordinary concrete. This paper presents a state-of-the-art review of the properties of CAC, including (1) the physical properties of coral aggregates; (2) the mechanical properties of CAC under uniaxial and multiaxial compression; and (3) the durability of CAC especially its chloride ion resistance and performance under drying-wetting cycles. To overcome the challenges of steel corrosion in marine environments, fiber-reinforced polymer (FRP) has been indicated to be a promising material for applications in CAC construction. The latest studies on the combination of FRP and CAC are reviewed, including the use of FRP tubes and bars.